Complement Mediated Endothelial Damage in Thrombotic Microangiopathies - Blasco, Miquel; Guillén-Olmos, Elena; Diaz-Ricart, Maribel; Palomo, Marta (Frontiers in Medicine, 2022)
Thrombotic microangiopathies (TMA) constitute a group of different disorders that have a common underlying mechanisim: the endothelial damage. These disorders may exhibit different mechanisms of endothelial injury depending on the pathological trigger. However, over the last decades, the potential role of the complement system (CS) has gained prominence in their pathogenesis. This is partly due to the great efficacy of complement-inhibitors in atypical hemolytic syndrome (aHUS), a TMA form where the primary defect is an alternative complement pathway dysregulation over endothelial cells (genetic and/or adquired). Complement involvement has also been demonstrated in other forms of TMA, such as thrombotic thrombocytopenic purpura (TTP) and in Shiga toxin-producing Escherichia coli hemolytic uremic syndrome (STEC-HUS), as well as in secondary TMAs, in which complement activation occurs in the context of other diseases. However, at present, there is scarce evidence about the efficacy of complement-targeted therapies in these entities. The relationship between complement dysregulation and endothelial damage as the main causes of TMA will be reviewed here. Moreover, the different clinical trials evaluating the use of complement-inhibitors for the treatment of patients suffering from different TMA-associated disorders are summarized, as a clear example of the entry into a new era of personalized medicine in its management.